Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a+b=c+d\Rightarrow a^2+2ab+b^2=c^2+2cd+d^2\)
\(\Rightarrow ab=cd\Rightarrow\left(a-b\right)^2=\left(c-d\right)^2\Rightarrow\left|a-b\right|=\left|c-d\right|\)
\(\Rightarrow\orbr{\begin{cases}a-b=c-d\\a-b=d-c\end{cases}\Rightarrow\orbr{\begin{cases}a=c\\a=d\end{cases}}}\)( kết hợp gt ) ....
\(\Rightarrow\)đpcm
Từ \(a^2+ab-6b^2=0\Rightarrow\left(a^2+3ab\right)-\left(2ab+6b^2\right)=0\)
\(\Leftrightarrow a\left(a+3b\right)-2b\left(a+3b\right)=0\Leftrightarrow\left(a+3b\right)\left(a-2b\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}a=-3b\\a=2b\end{cases}}\)
Với \(a=-3b\Rightarrow S=\frac{-3b+3b}{5.\left(-3b\right)+b}=\frac{0}{-14b}=0\)
Với \(a=2b\Rightarrow S=\frac{2b+3b}{5.2b+b}=\frac{5b}{11b}=\frac{5}{11}\)